Pengaruh penggunaan mulsa plastik hitam perak dengan berbagai bentuk bedengan pada pertumbuhan tanaman cabai merah (Capsicum annuum.L) - Galang Diki Trenaldi; Yusmaidar Sepriani; Dini Hariyati Adam; Ika Ayu Putri Septyani (PT ADRIANI MANDIRI PUBLISHER, 2026)
In the dry season, increasing temperatures cause high soil temperatures, low soil moisture and can result in soil loss of water through evaporation. Thus, the growth of red chili plants is less than optimal. One of the cultivation techniques that can increase red chili production is by modifying the microclimate around the plant by using mulch. The purpose of this study was to determine the effect of silver black plastic mulch with various forms of beds on the growth of red chili plants, so that it can be seen that the use of silver black plastic mulch is suitable for use on red chili plants. The research was carried out in the Afdeling 2 Plantation area, Kec. Blade (West Kab. Labuhanbatu. In October 2021 to April 2022. This study used a Randomized Block Design (RAK). The study used a factor of 4 treatments of different types of beds in the use of silver black plastic mulch which consisted of no black silver plastic mulch with a convex shape. , without black silver plastic mulch flat shape, with black silver plastic mulch convex shape, with black silver plastic plastic mulch flat shape repeated 5 times so that 20 experimental units are obtained. The results showed that the use of black silver plastic mulch with various beds had a significant effect on height. number of plants, number of leaves, and leaf area of ​​red chili plants at observations 4, 6 and 8 WAP. The best use of silver black plastic mulch used in the cultivation of red chili plants is using silver black plastic mulch in the form of flat beds which shows results with an average value average 21.00 (2MST), 40.25 (4MST), 53.88 (6MST), 65.92( 8MST) for plant height, the mean values ​​were 10.85 (2MST), 30.80 (4MST), 87.25 (6MST), 113.15 (8MST) for the number of leaves